Ranking of hydropower projects based on sustainability criteria in India using multicriteria decision making methods - Anuja Shaktawat; Shelly Vadhera (International Journal of Applied Power Engineering (IJAPE), 2021)
Assessment of hydropower projects with respect to sustainability criteria is a multidimensional and a complex issue that decision makers usually face during planning process. In hydropower projects, it is important to consider technical, environmental and social parameters instead of purely economic ones for sustainability assessment and decision making. Multi-criteria decision making (MCDM) methods offer a practical approach to a problem having conflicting criteria. The flexibility to consider several criteria and objectives simultaneously made MCDM methods well accepted in the field of energy planning. This paper aims for applicability of MCDM methods which will facilitate the decision makers to select the most sustainable hydropower projects by making real and logical choices based on various sustainability criteria. For comprehensively rank hydropower projects of Indian region based on sustainability criteria four MCDM methods are applied i.e., analytic hierarchy process (AHP), technique for order of preference by similarity to ideal solution (TOPSIS), preference ranking organization method for enrichment evaluations (PROMETHEE II) and elimination and choice translating reality (ELECTRE III). To ensure better decision making the eight criteria selected are compatible to the sustainable development of hydropower projects.